Learning lexigraphy: a psycholinguistic perspective - Mamani Quispe, Luis Alberto (1999)
Lexigraphy is that part of orthography that deals with the correct use of letters. From it we know that "bacilo" is written with "b" and with "c"; "vara", with "v"; "hulla", etc. In the present work, we will focus on what traditionally bears the titles "Use of V", "Use of z", "Use of j", etc.